2012
DOI: 10.1126/science.1226960
|View full text |Cite
|
Sign up to set email alerts
|

Synchronizing Nuclear Import of Ribosomal Proteins with Ribosome Assembly

Abstract: Ribosomal proteins are synthesized in the cytoplasm, before nuclear import and assembly with ribosomal RNA (rRNA). Little is known about coordination of nucleocytoplasmic transport with ribosome assembly. Here, we identify a transport adaptor, symportin 1 (Syo1), that facilitates synchronized coimport of the two 5S-rRNA binding proteins Rpl5 and Rpl11. In vitro studies revealed that Syo1 concomitantly binds Rpl5-Rpl11 and furthermore recruits the import receptor Kap104. The Syo1-Rpl5-Rpl11 import complex is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
173
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 104 publications
(176 citation statements)
references
References 50 publications
2
173
0
1
Order By: Relevance
“…A specific feature of LSU assembly is the incorporation of a preformed 5S RNP ( Figure 2J) comprising the 5S RNA and the rproteins uL5 and uL18. Formation of the 5S RNP is facilitated by the transport adaptor Syo1, which couples nuclear import of uL5 and uL18 with 5S rRNA association [90,91]. The subsequent incorporation of the 5S RNP module involves the Rpf2-Rrs1 heterodimer and has already occurred within the Nsa1-defined particle [25,86,[92][93][94] (Figure 2K).…”
Section: Assembly Of the Lsumentioning
confidence: 99%
“…A specific feature of LSU assembly is the incorporation of a preformed 5S RNP ( Figure 2J) comprising the 5S RNA and the rproteins uL5 and uL18. Formation of the 5S RNP is facilitated by the transport adaptor Syo1, which couples nuclear import of uL5 and uL18 with 5S rRNA association [90,91]. The subsequent incorporation of the 5S RNP module involves the Rpf2-Rrs1 heterodimer and has already occurred within the Nsa1-defined particle [25,86,[92][93][94] (Figure 2K).…”
Section: Assembly Of the Lsumentioning
confidence: 99%
“…It has been shown that karyopherins or chaperones interact with ribosomal proteins to maintain their solubility and also facilitate their loading into nascent ribosomal subunits (33)(34)(35)(36)(37)(38)(39)(40)(41)(42).…”
Section: Figure 2 the Function Of Bcp1 Is Tightly Connected With Manmentioning
confidence: 99%
“…Rrb1 has direct interaction with Rpl3 (uL3), and overexpression of Rrb1 increased the level and nuclear accumulation of Rpl3 (36). Syo1 facilitates coimport of Rpl5 (uL18) and Rpl11 (uL5) and chaperones 5S RNP assembly (33,38). Acl4 is a chaperone of Rpl4 (uL4) and accompanies Rpl4 from the cytoplasm to the loading onto the pre-60S in the nucleus (39,41).…”
Section: Bcp1 Is a Chaperone Of Rpl23 And Required To Maintain Thementioning
confidence: 99%
“…In contrast, 5S rRNA is transcribed separately by RNA polymerase III, and its precursor matures to the 5S rRNA independently from the pre-35S RNA processing pathway 9,10 . Subsequently, 5S rRNA recruits two r-proteins, L5 and L18 (previously called Rpl11 and Rpl5 in yeast, respectively), to form the 5S ribonucleoprotein (RNP) particle, which becomes incorporated en bloc into the evolving pre-60S subunit [11][12][13] . In the mature 80S ribosome, the 5S rRNA is located within the central protuberance of the 60S subunit, where it is involved in intersubunit interactions, mediated by a number of protein-RNA and RNA-RNA contacts 14,15 .…”
mentioning
confidence: 99%